Hospitalizations trends and co-infection patterns for respiratory virus infections in children in central China 2015 to 2023: a longitudinal surveillance study - Bowen Dai; Chong Chen; Yuanfang Shen; Shouhang Chen; Ruyu Zhang; Chenyu Wang; Jiaying Zheng; Qiujing Liang; Qingmei Wang; Yaodong Zhang; Yuefei Jin; Fang Wang; et al. (BMC Infectious Diseases)
Abstract This study presents a comprehensive epidemiological analysis of respiratory viral infections in Henan Province, China, from 2015 to 2023, encompassing 183,771 reported cases. The predominant pathogens included influenza A virus (Flu A), accounting for 58.66% of infections, followed by influenza B virus (Flu B), respiratory syncytial virus (RSV), parainfluenza virus (PIV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), human rhinovirus (HRV), was 19.44%, 12.00%, 9.10%, 0.44%, and 0.37%, respectively. A significantly higher detection rate was observed in males compared to females (57.22% vs. 42.78%; χ2 < 0.001). Co-infections were documented in 2.16% of cases, with the most prevalent combination being Flu A + Flu B. Notably, the co-infection cases peaked in 2023, likely due to the relaxation of non-pharmaceutical interventions (NPIs) following the COVID-19 pandemic. The detailed wavelet analysis revealed distinct periodic patterns for various respiratory viruses, highlighting the necessity of adaptable vaccination strategies. These findings underscore the dynamic nature of respiratory viral epidemiology and emphasize the significance of continuous surveillance and targeted public health interventions, particularly for high-risk populations. Future research should further investigate the implications of these trends on long-term respiratory health outcomes and inform effective strategies to mitigate the burden of respiratory infections.